A Chern-Simons model for baryon asymmetry - Risto Raitio (Nuclear Physics B, 2023)
In search of a phenomenological model that would describe physics from Big Bang to the Standard Model (SM), we propose a model with the following properties (i) above an energy about Λcr>1016 GeV there are Wess-Zumino supersymmetric preons and Chern-Simons (CS) fields, (ii) at Λcr∼1016 GeV spontaneous gauge symmetry breaking takes place in the CS sector and the generated topological mass provides an attractive interaction to equal charge preons, (iii) well below 1016 GeV the model reduces to the standard model with essentially pointlike quarks and leptons, having a radius ∼1/Λcr≈10−31 m. The baryon asymmetry turns out to have a fortuitous ratio nB/nγ≪1.